Natural phospholipids: Occurrence, biosynthesis, separation, identification, and beneficial health aspects. Issue 2 (19th January 2019) - Ali, Abdelmoneim H.; Zou, Xiaoqiang; Abed, Sherif M.; Korma, Sameh A.; Jin, Qingzhe; Wang, Xingguo
ABSTRACT: During the last years, phospholipids (PLs) have attracted great attention because of their crucial roles in providing nutritional values, technological and medical applications. There are considerable proofs that PLs have unique nutritional benefits on human health, such as reducing cholesterol absorption, improving liver functions, and decreasing the risk of cardiovascular diseases. PLs are the main structural lipid components of cell and organelle membranes in all living organisms, and therefore, they occur in all organisms and the derived food products. PLs are distinguished by the presence of a hydrophilic head and a hydrophobic tail, consequently they possess amphiphilic features. Due to their unique characteristics, the extraction, separation, and identification of PLs are critical issues to be concerned. This review is focused on the content of PLs classes in several sources (including milk, vegetable oils, egg yolk, and mitochondria). As well, it highlights PLs biosynthesis, and the methodologies applied for PLs extraction and separation, such as solvent extraction and solid-phase extraction. In addition, the determination and quantification of PLs classes by using thin layer chromatography, high-performance liquid chromatography coupled with different detectors, and nuclear magnetic resonance spectroscopy techniques.